Cell wall polysaccharide-mediated cadmium tolerance between two Arabidopsis thaliana ecotypes - Xiao, Yan; Wu, Xiuwen; Liu, Dong; Yao, Junyue; Liang, Guihong; Song, Hai-Xing; Ismail, Abdelbagi M.; Luo, Jin-Song; Zhang, Zhenhua (Frontiers Media, 2020)
Cadmium (Cd) is a toxic metal element and the mechanism(s) underlying Cd tolerance in plants are still unclear. Increasingly more studies have been conducted on Cd binding to plant cell walls (CW) but most of them have focused on Cd fixation by CW pectin, and few studies have examined Cd binding to cellulose and hemicellulose. Here we found that Cd binding to CW pectin, cellulose, and hemicellulose was significantly higher in Tor-1, a Cd tolerant A. thaliana ecotype, than in Ph2-23, a sensitive ecotype, as were the concentrations of pectin, cellulose, and hemicellulose. Transcriptome analysis revealed that the genes regulating CW pectin, cellulose, and hemicellulose polysaccharide concentrations in Tor-1 differed significantly from those in Ph2-23. The expressions of most genes such as pectin methyl esterase inhibitors (PMEIs), pectin lyases, xyloglucan endotransglucosylase/hydrolase, expansins (EXPAs), and cellulose hydrolase were higher in Ph2-23, while the expressions of cellulose synthase-like glycosyltransferase 3 (CSLG3) and pectin ethyl esterase 4 (PAE4) were higher in Tor-1. The candidate genes identified here seem to regulate CW Cd fixation by polysaccharides. In conclusion, an increase in pectin demethylation activity, the higher concentration of cellulose and hemicellulose, regulated by related genes, in Tor-1 than in Ph2-23 are likely involved in enhanced Cd CW retention and reduce Cd toxicity.